EXTRACTION AND IDENTIFICATION OF COMPOUNDS FROM BIOETHANOL PRODUCTION WASTE WITH POTENTIAL AS PEST CONTROL AGENTS BY LC-MS/MS - Etyn Yunita; Sumarlin La Ode; Dhea Aprilliyani; Yudi Harsono; Pamungkas Riski Ferdian; Anang Setiawan Achmadi; Nurhasni Nurhasni; Mia Azizah (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
Bioethanol production generates waste by-products that may contain various valuable chemical compounds, many of which have not yet been fully explored or utilized. Among these by-products, liquid waste, commonly known as vinasse, is one of the most frequently processed and reused forms. This study aimed to extract and identify compounds from bioethanol production waste, particularly those with potential as pest control agents. Chemical profiling was conducted using liquid chromatography–tandem mass spectrometry (LC-MS/MS). Analysis of samples extracted with n-hexane, ethyl acetate, ethanol, and water revealed several putative bioactive compounds with pesticidal activity. Notable identified compounds included DEET (N,N-diethyl-m-toluamide) (m/z = 192.1388), loliolide (m/z = 197.1178), (S)-reticuline (m/z = 330.1705), 3,5,6-trihydroxy-5-(hydroxymethyl)-2-methoxy-2-cyclohexen-1-one (m/z = 206.0712), and cuscohygrine (m/z = 225.1983). These compounds are known to exert various biological activities, including antibacterial, antifungal, and insect-repellent effects, each operating through distinct mechanisms. However, further functional validation through field implementation studies is necessary to evaluate the effectiveness and long-term sustainability of their application, particularly regarding the presence of DEET in the samples.